2012
DOI: 10.1080/10498850.2011.586489
|View full text |Cite
|
Sign up to set email alerts
|

Levels of Selected Metals in Albacore (Thunnus alalunga, Bonnaterre, 1788) from the Eastern Mediterranean

Abstract: Albacore has been exported mainly to Europe from Turkey. To evaluate the possible health risks and provide information for surveillance programs, concentrations of cadmium, mercury, and lead were determined in albacore from the Eastern Mediterranean Sea. Of the 34 individuals, 25 contained mercury and 9 contained cadmium above the permissible limits set by the European Union (1 mg/kg and 0.1 mg/kg, respectively). None of the samples contained lead above the limit (0.3 mg/kg). It was concluded that concentratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 21 publications
(29 reference statements)
0
4
1
Order By: Relevance
“…In the literature, lead bioaccumulation in tuna species shows highly variable results. Mol et al [ 34 ] detected the content of 0.220 ± 0.007 mg kg −1 wet wt as highest Pb content in T. alalunga specimens caught from the Eastern Mediterranean, in contrast to the highest Pb content detected in the present study (0.557 mg kg −1 wet wt). Storelli [ 45 ] and Besada et al [ 49 ] reported the highest Pb content in T. alalunga caught from the central Mediterranean Sea and the Atlantic Ocean as 3.130 and 0.012 mg kg −1 wet wt, respectively.…”
Section: Discussioncontrasting
confidence: 87%
See 1 more Smart Citation
“…In the literature, lead bioaccumulation in tuna species shows highly variable results. Mol et al [ 34 ] detected the content of 0.220 ± 0.007 mg kg −1 wet wt as highest Pb content in T. alalunga specimens caught from the Eastern Mediterranean, in contrast to the highest Pb content detected in the present study (0.557 mg kg −1 wet wt). Storelli [ 45 ] and Besada et al [ 49 ] reported the highest Pb content in T. alalunga caught from the central Mediterranean Sea and the Atlantic Ocean as 3.130 and 0.012 mg kg −1 wet wt, respectively.…”
Section: Discussioncontrasting
confidence: 87%
“…Evidences of pollution exist regarding toxic heavy metals, e.g., [ 30 , 31 , 32 ] and nutrients e.g., [ 33 ]. However, publications on the concentrations and the human health risks assessment of Hg, Cd, and Pb in albacore from the Aegean Sea region are very limited [ 34 ]. Therefore, the objective of the present work was to study the concentrations of Hg, Cd, and Pb in albacore tuna ( T. alalunga ) samples from two fishing grounds in the Aegean Sea, in order to evaluate the possible risks for human health and to ensure that the fish, fresh or processed, is safe for human consumption.…”
Section: Introductionmentioning
confidence: 99%
“…Also in the raw fish material from Turkish waters which can be used for canning elevated concentrations of heavy metals have been reported (Celik et al 2004;Dalman et al 2006;Ersoy et al 2010;Mendil et al 2010;Mol et al 2012;Tuzen 2009;Uluozlu et al 2007;Yildirim et al 2009;Yilmaz et al 2010). …”
Section: Introductionmentioning
confidence: 95%
“…The compared models are listed below in Table 2. The first data set represents the level of mercury in 34 albacores caught in the Eastern Mediterranean used by [15]. The second data set consists of thirty successive values of March precipitation (in inches) in Minneapolis/St Paul by [10].…”
Section: Applicationmentioning
confidence: 99%